Financial Performance Comparison Pre and Post-Acquisition of Indonesian Stock Exchange Companies - Loura, Berlia; Heniwati, Elok; Kurniawan, Rudy (DINASTI RESEARCH, 2024)
The business landscape in Indonesia is experiencing heightened competition compared to previous periods. Companies must devise robust strategies to mitigate potential downturns caused by various factors. One viable strategy is acquisitions. However, acquisitions can fail if not meticulously planned and executed. This study analyzes financial performance before and after acquisitions using financial ratios such as Current Ratio (CR), Total Assets Turnover (TATO), Return on Equity (ROE), and Debt to Equity Ratio (DER). The observation period covers two years before and three years after the acquisition (t-2 and t+3). We will compare the financial performance of companies listed on the Indonesia Stock Exchange (IDX) that have undergone acquisitions. The research adopts a comparative approach with a quantitative methodology. The study population consists of fifteen companies listed on the IDX that completed acquisitions between 2018 and 2019. Evaluations are conducted using the Wilcoxon Sign Rank Test and Paired Sample T Test. Although the study found no significant changes in financial performance before and after acquisitions during the observation period, the CR ratio at t+3 compared to t-1 and the DER ratio at t+1 compared to t-1 showed significant differences.